Prevalence of periodontal disease findings from panoramic radiographs in the Radiology Department of RSGMP Hasanuddin University in 2023: Prevalensi temuan penyakit periodontal dari radiografi panoramik di Departemen Radiologi RSGMP Universitas Hasanuddin pada tahun 2023 - Barunawaty Yunus; Nurul Sakinah (Makassar Dental Journal, 2024)
Radiograph examination is one of the important examinations in diagnosing, determining the prognosis, and evaluating the treat-ment outcome of periodontal disease. Alveolar bone changes can indicate the onset and progression of periodontal disease. This study aimed to determine the prevalence of periodontal disease from panoramic radiographs in the Radiology Department of RSGMP Unhas in 2023. Descriptive observational study through panoramic radiography photo data was conducted in 2023, then the results were presented in the form of tables and diagrams. The most common periodontal disease was mild periodontitis at 37.9% and was found more in women than men. Periodontal disease based on age group, obtained that the highest prevalence in the age group 46-65 years at 42.3%. It is concluded that the prevalence of periodontal disease is still relatively high due to the low level of knowledge and public awareness of oral health maintenance and oral health services that have not been implemen-ted optimally.